The Islamic Kingdom of Banten: An Analysis of Facts and Artifacts - Hajar, Imam Ibnu; Sya’ie, Akhmad Najibul Khairi; Hawari, Muhammadudy Hisyam; Rabbani, Muhammad Syiham (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
As a country composed of numerous islands, Indonesia once had many maritime-based kingdoms. One of them was the Kingdom of Banten, located at the westernmost tip of Java Island. This kingdom played a vital role both in economic development through its commercial trading port and in the spread of Islam. Banten became one of the most important Islamic kingdoms in the country, with a bustling trade port at the time. One contributing factor was the Portuguese occupation of Malacca and the decline of another major Islamic maritime kingdom, the Demak Sultanate. Historians have attempted to uncover the greatness of this Islamic kingdom through various methods and theories. Several investigations, explorations, and research efforts have been conducted by studying related historical documents, artifacts, and the ruins of the royal palace to find authentic evidence of the kingdom’s power and significance. These efforts reveal that the kingdom attracted not only local and national traders but also many European explorers. The existing evidence shows that it was the largest and most significant Islamic maritime kingdom on the island of Java.